Sonographic evaluation of adrenal size in neonates (23 to 41 weeks of gestation) - Shigeo Iijima (BMC, 2018)
Abstract Background Fetal adrenal gland size is known to have a positive correlation with both gestational age and estimated body weight. In contrast, some clinical observations suggest that maturation of the adrenal stress response occurs after 30 weeks of gestation. In this study, adrenal gland size at birth in extremely preterm to term neonates was investigated using ultrasonography to evaluate the adrenal developmental pattern and the impact of prematurity and perinatal factors. Methods The area of the right adrenal gland was measured in the first 3 h of life in 350 neonates and corrected for birth weight (BW) to determine the corrected adrenal area index (cAI). The neonates were subdivided into three groups: group 1 (before 30 weeks of gestation), group 2 (30 to 36 weeks), and group 3 (after 37 weeks). Differences in the cAI among the 3 groups were compared to estimate the impact of perinatal factors. Results The adrenal gland size was measurable in all neonates with gestational age ranging from 23 to 41 weeks. Right adrenal gland area was highly correlated with BW (r = 0.75, p < 0.01). cAI showed a significant negative correlation with gestational age in group 1 (r = − 0.67, p < 0.01), whereas it showed no correlation with gestational age in both groups 2 and 3. As for the impact of perinatal parameters on cAI, only gestational age in group 1 and only fetal distress in group 2 were correlated with cAI. In group 3, perinatal parameters such as fetal distress and low Apgar score were correlated with cAI. Conclusions The present study demonstrated that the developmental pattern of fetal adrenal gland was different before and after 30 weeks of gestation, suggesting that the magnitude of adrenal stress response might mature after 30 weeks of gestation.